Capsaicin protects cardiomyocytes against lipopolysaccharide-induced damage via 14-3-3γ-mediated autophagy augmentation - Qiao, Yang; Wang, Liang; Hu, Tianhong; Yin, Dong; He, Huan; He, Ming (Frontiers in Pharmacology, 2021)
Background: The myocardium is susceptible to lipopolysaccharide (LPS)-induced damage in sepsis, and cardiac dysfunction is a leading cause of mortality in patients with sepsis. The changes in cardiomyocyte autophagy in sepsis and the effects and mechanism of action of capsaicin (Cap) remain unclear. Methods and Results: The potential pathway of 14-3-3γ-dependent autophagy and the effects and mechanisms of Cap were studied in LPS-induced injury to primary cultured neonatal rat cardiomyocytes. The results showed that cardiomyocyte viability decreased, lactate dehydrogenase and creatine kinase activities increased, 14-3-3γ expression was downregulated, and autophagy was inhibited after LPS challenge. Cap pretreatment augmented autophagy by upregulating 14-3-3γ expression and activating AMP-activated protein kinase (AMPK) and unc-51 like autophagy-activating kinase 1 (ULK1), suppressing mammalian target of rapamycin (mTOR), alleviating cardiac dysfunction and improving the inflammation response, whereas pAD/14-3-3γ-shRNA nullified the above effects. Cap pretreatment also decreased the levels of IL-1β, TNF-α, IL-6, and IL-10; suppressed intracellular oxidative stress; reduced the intracellular/mitochondrial reactive oxygen species (ROS); balanced GSH/GSSG; increased GSH-Px, catalase, and SOD activities; and decreased MDA contents. It also increased ATP content, activated complex Ⅰ and complex Ⅲ, stabilized the mitochondrial membrane potential, and decreased the mitochondrial permeability transition pore opening, thereby improving mitochondrial function. Conclusion: Pretreatment with Cap can regulate autophagy by upregulating 14-3-3γ expression, inhibiting oxidative stress and inflammation, maintaining mitochondrial function, and protecting cardiomyocytes against LPS-induced injury.